2012 19th International Symposium on Temporal Representation and Reasoning 2012
DOI: 10.1109/time.2012.13
|View full text |Cite
|
Sign up to set email alerts
|

Automata-based Verification of Linear Temporal Logic Models with Bounded Variability

Abstract: Abstract-A model has variability bounded by v/k when the state changes at most v times over any linear interval containing k time instants. When interpreted over models with bounded variability, specification formulae that contain redundant metric information-through the usage of next operators-can be simplified without affecting their validity. This paper shows how to harness this simplification in practice: we present a translation of LTL into Büchi automata that removes redundant metric information, hence m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2014
2014
2016
2016

Publication Types

Select...
1
1

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 19 publications
0
7
0
Order By: Relevance
“…Even if the asymptotic worst-case complexity of MTL over discrete time does not change with bounded variability, our previous work [21,22] indicates that the complexity decreases in practice for MTL formulas that can be expressed with certain syntactic restrictions, where the exponential blow-up due to succinct encoding of constants is essentially avoided. Therefore, we can still assert that bounded variability may help simplify MTL decidability in some specific cases.…”
Section: Complexity In Special Casesmentioning
confidence: 99%
See 2 more Smart Citations
“…Even if the asymptotic worst-case complexity of MTL over discrete time does not change with bounded variability, our previous work [21,22] indicates that the complexity decreases in practice for MTL formulas that can be expressed with certain syntactic restrictions, where the exponential blow-up due to succinct encoding of constants is essentially avoided. Therefore, we can still assert that bounded variability may help simplify MTL decidability in some specific cases.…”
Section: Complexity In Special Casesmentioning
confidence: 99%
“…One approach to restricting MTL expressiveness consists in introducing semantic constraints. We pursued this approach in previous work [18,21,22], where we showed that validity of MTL over dense time becomes decidable under the restriction of bounded variability. A nonnegative integer v and a time duration V identify all models with variability bounded by v/V : models where there are no more than v events (such as change of state) over any interval of length V .…”
Section: Reaping the Benefits Of Bounding Variabilitymentioning
confidence: 99%
See 1 more Smart Citation
“…Bounded variability is a natural semantic restriction over dense time, which has been applied to various formalisms including timed automata [27], duration calculus [10], and, in our previous work, MTL [12]. Recently, we also applied it to LTL over discrete time; while it is obvious that every discrete-time model has bounded variability (given by the fixed duration associated with one discrete time unit), in [14,15] we showed how the LTL validity problem can be simplified under the assumption that only v < V change events happen every V discrete time steps. Therefore, bounded variability can be a simplifying assumption also for discrete time.…”
Section: Related Workmentioning
confidence: 99%
“…The validity of ψ ⇒ B v,V can thus be decided in singly exponential time (Lemma 14), as opposed to BV N (v, V ) or the validity of φ which are EXPSPACE-complete: solving them for a generic φ takes time doubly exponential in |φ|. We can thus decide whether ψ ⇒ B v,V is valid in singly exponential time; if it is, φ has bounded variability a fortiori, and hence we can study its validity with the simplified algorithms [14,15].…”
Section: Simpler Bounded Variability Over Discrete Timementioning
confidence: 99%